(untitled) (Plant Tissue Culture and Biotechnology, 2026)
The excessive use of synthetic herbicides has raised environmental and health concerns, necessitating the search for eco-friendly alternatives. Sapodilla (Manilkara zapota L.), has shown potential as a natural herbicide due to its reported phytotoxic effects. This study evaluates the bioherbicidal potential of M. zapota leaf crude extract and investigates the molecular mechanism of its bioactive compounds through Molecular Docking (MD) and Molecular Dynamic Simulations (MDS). MD were performed to analyze the binding affinity of key phytochemicals with essential plant growth-related enzymes, such as acetohydroxyacid synthase (AHAS), cellulose synthase (CS), glutamine synthase (GLS) and the D1 protein of photosystem II (PSIID1). The analyses confirmed the strong interaction of specific bioactive compounds with target enzymes, suggesting their potential as natural herbicidal agents. The herbicidal effects of M. zapota extracts were assessed on selected weed species Parthenium hysterophorus through seed germination inhibition. The study highlights M. zapota as a promising source of bioherbicidal compounds, offering an environmentally sustainable alternative to synthetic herbicides. Plant Tissue Cult. & Biotech. 35(2): 427-446, 2025 (December)